Establishment of entrepreneurial Activities in the field of green tourism in European countries - Petruk, Tatyana; Skliar, Heorhii; Shukanova, Anzhela; Yemtsev, Victor; Shykerynets, Vasyl (My University, 2021)
The article considers the current issue of active and necessary development of entrepreneurship in the field of green tourism in European countries. A statistical analysis of the demand for green tourism in the EU countries and the dynamics of generating profits from green tourism were conducted. Practical tools for engaging rural people in green entrepreneurship activities are substantiated. A new structure for a cluster of entrepreneurial entities in rural green tourism has been proposed.
Keywords: entrepreneurshipe; green Tourist; tourism Industry; tourism product; cluster of business entities; national interests; підприємництво; зелений туризм; індустрія туризму; туристичний продукт; суб'єкти господарювання; національні інтереси; кафедра економіки праці та менеджменту